Negative Effects of Redundant Targets. - White, Alex L.; Palmer, John; Sanders, Genevieve; Hossain, Jannat; Zabinsky, Zelda B. (Journal of Experimental Psychology. Human Perception & Performance, 2026)
The visual system can encode many stimuli simultaneously, but there are limits to how well multiple objects can be identified in parallel. At the extreme, some objects might have to be identified serially. The redundant target paradigm is one tool for distinguishing specific parallel and serial models. It compares responses to displays containing one target versus displays containing two targets. The typical result is a positive redundant target effect: faster correct responses to two targets, as predicted by many parallel models. Here, we generalize three standard models to account for response accuracy as well as speed. Surprisingly, two models predict a reversal of the redundant target effect (slower responses to two targets than to one target): the generalized standard serial model and a specific form of a fixed-capacity parallel model. To test that prediction, we measured performance for three different judgments of written words: color detection, lexical decision, and semantic categorization. The color task yielded positive redundant target effects, which reject the standard serial model. The semantic task yielded consistently negative effects, which are consistent with either the standard serial model or some limited-capacity parallel models. Thus, redundant targets can have negative effects, and they demonstrate limits that impair simultaneous recognition of two words. Public Significance Statement: The visual environment often contains many relevant objects, from faces in a crowd to words on a page. Here, we improve an experimental test of whether you can process more than one such stimulus at a time. The results reveal limits to how well you can recognize two written words simultaneously.